Quantum phases of the planar antiferromagnetic J₁-J₂-J₃ Heisenberg model - Reuther, Johannes (2011)
We present results for a complementary analysis of the frustrated planar J₁-J₂-J₃ spin-1/2 quantum antiferromagnet (AFM). Using dynamical functional renormalization group, high-order-coupled cluster calculations, and series expansion based on the flow equation method, we have calculated generalized momentum-resolved susceptibilities, the ground-state energy, the magnetic-order parameter, and the elementary excitation gap. From these, we determine a quantum phase diagram that shows a large window of a quantum paramagnetic (QP) phase situated among the Néel, spiral, and collinear states, which are present already in the classical J₁-J₂-J₃ AFM. Our findings are consistent with substantial plaquette correlations in the QP phase. The extent of the QP region is found to be in satisfying agreement between the three different approaches we have employed.